2001
DOI: 10.4049/jimmunol.166.10.5889
|View full text |Cite
|
Sign up to set email alerts
|

CD44-Deficient Mice Exhibit Enhanced Hepatitis After Concanavalin A Injection: Evidence for Involvement of CD44 in Activation-Induced Cell Death

Abstract: Administration of Con A induces severe injury to hepatocytes in mice and is considered to be a model for human hepatitis. In the current study, we investigated the role of CD44 in Con A-induced hepatitis. Intravenous administration of Con A (20 mg/kg) caused 100% mortality in C57BL/6 CD44-knockout (KO) mice, although it was not lethal in C57BL/6 CD44 wild-type (WT) mice. Administration of lower doses of Con A (12 mg/kg body weight) into CD44 WT mice induced hepatitis as evident from increased plasma aspartate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 34 publications
3
81
1
Order By: Relevance
“…If CD44-stimulated NKT cells are protected from the TCR-mediated AICD that typically follows lymphocyte activation, persistent NKT cell stimulation and immune dysfunction could thus follow. To contrast with this idea, a nice study by Nagarkatti and colleagues (58) showed in a model of ConA-induced hepatitis that expression of CD44 correlated with less severe disease. Furthermore, CD44 expression in that report correlated with increased AICD.…”
Section: Discussionmentioning
confidence: 94%
“…If CD44-stimulated NKT cells are protected from the TCR-mediated AICD that typically follows lymphocyte activation, persistent NKT cell stimulation and immune dysfunction could thus follow. To contrast with this idea, a nice study by Nagarkatti and colleagues (58) showed in a model of ConA-induced hepatitis that expression of CD44 correlated with less severe disease. Furthermore, CD44 expression in that report correlated with increased AICD.…”
Section: Discussionmentioning
confidence: 94%
“…7F). These changes were reversed by treating DN32.D3 cells with the FXR 4 The online version of this article contains supplemental material. ligand 6E-CDCA (Fig.…”
Section: Fxr/shp Directly Regulates Opn Gene Expression On Activated mentioning
confidence: 99%
“…In a second set of experiments, FXR Ϫ/Ϫ and WT mice were administered with a sublethal dose of Con A (10 mg/kg), with or without pretreatment with the same agent as described above. Mice were then sacrificed under pentothal anesthesia at 4,8,24, and 48 h after Con A administration and blood and livers were collected. Plasma aspartate aminotransferase (AST) was used as a marker of hepatic injury.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of apoptotic cells was determined by evaluating z500 cells per treatment in triplicate. To confirm the results of morphologic analysis, TUNEL method was used as described elsewhere (66).…”
Section: Detection Of Thc-induced Apoptosis In Vitromentioning
confidence: 99%